Tasmim Hajat Tasmim Dalil al-Musafir li al-Tawasul bi al-Lughah al-Arabiyyah 'Abra al-Hawatif al-Zakiyyah li al-Mutawwifin - Sahrir, Muhammad Sabri; zubir, Muhamad Azhar; Ismail, Taufik (Penerbit UPSI, Perak Darul Ridzuan., 2021)
Tasmim Hajat Tasmim Dalil al-Musafir li al-Tawasul bi al-Lughah al-Arabiyyah 'Abra al-Hawatif al-Zakiyyah li al-Mutawwifin. A book chapter in a published book by UPSI.